SUSTAINABLE AGRITOURISM DEVELOPMENT STRATEGIES IN MAGELANG REGENCY: A SWOT ANALYTICAL PERSPECTIVE - Destiningsih, Rian; Achsa, Andhatu (Universitas Tidar, 2025)
This study examines strategies for developing agritourism in Magelang Regency, Indonesia, as a driver of sustainable rural economic transformation. Agritourism integrates agricultural potential, cultural heritage, and tourism demand to enhance household income, community empowerment, and regional competitiveness. The research aims to formulate strategic directions to improve competitiveness and local economic benefits amid weak branding, uneven facilities, and seasonal dependency. Using descriptive and quantitative methods, the study applied SWOT and Internal-External (IE) Matrix analyses that integrate socio-economic, environmental, and technical dimensions. Data were collected from 100 tourists and 18 stakeholders, including agrotourism managers and SMEs. The results show that Magelang agritourism is positioned in Cell V of the IE Matrix, indicating a growth and build strategy. The dominant S-O strategy emphasizes digital promotion, attraction optimization, product diversification, and branding improvement. Empirical findings confirm that agrotourism generates multiplier effects through income growth, employment, SME competitiveness, and environmental conservation. The study contributes a holistic analytical framework and provides policy implications for sustainable and competitive agritourism development.